Educators as transformative intellectuals: Taiwanese teacher activism during the national curriculum controversy. Issue 2 (15th March 2018) - Hung, Cheng-Yu
ABSTRACT: In early 2014, a group of senior high school teachers initiated a series of campaigns to fight against the government's imposition of a revised history and citizenship education curriculum, an unprecedented display of opposition in the history of public schools in Taiwan. They rose above the traditional stereotype of the schoolteacher common across many societies in Asia and challenged the pro-reunification and Chinese ethnocentric setting underlying the new educational proposals. Drawing upon Giroux's writings on teachers as transformative intellectuals, this article looks into the social activism of 12 teachers from the campaign and the impact this movement had on their classroom practices. While "the language of critique" and "the language of possibility" are defined by Giroux as the two crucial components a critical educator should possess, these Taiwanese activist teachers appeared to demonstrate a more nuanced view by separating their activism from their professionalism in front of students and preventing themselves from incorporating the personal social movement experience into their classroom teaching. Moreover, our findings also suggest that elements of Confucianism – deeply rooted in Taiwanese society – have shaped these teachers' involvement in activism in important ways.